Subjects and basis of legal responsibility in the pharmaceutical sphere of Ukraine - O. H. Aleksieiev (Zaporozhye State Medical University, 2018)
The purpose of the work is to determine the subjects of legal relations arising in the application of measures of legal liability for violation of pharmaceutical law and the grounds for its application. Materials and methods. The research material is a modern regulatory and legal framework of the pharmaceutical sector in the healthcare industry, as well as judicial practice in cases of bringing to justice the violators of pharmaceutical legislation. During the work, information retrieval, analysis, systematization and generalization methods were used. Results. On the basis of the analysis, a group of subjects of legal responsibility in the pharmaceutical field was suggested for further scientific discussion and discussion. Conclusions. The legal liability of subjects of pharmaceutical legal relations is an extremely important factor in preventing attacks on the legal rights of citizens to provide high-quality, safe and affordable drugs and medical products. The main groups of subjects of legal responsibility in the pharmaceutical sphere of offenses include pharmaceutical workers; pharmacies; business entities operating in the pharmaceutical and related fields; officials of the State Service of Ukraine on Drugs and Drug Control and other state regulatory and law enforcement agencies.